2008
DOI: 10.3122/jabfm.2008.05.070040
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Family Continuity with Infant Health Service Use

Abstract: Purpose: Continuity of care is a fundamental component of family medicine that has been shown to improve health care quality. Family continuity, when different family members are seen by the same clinician or practice, has not been well studied.Methods: We performed a retrospective cohort study of Medicaid enrollees in Oregon using administrative data. Infants were determined to have family continuity if they received well-baby care at the same clinic as that in which their mothers received prenatal care.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Continuity of carer is a critical component of primary health care known to improve the quality of service delivery [40]. Studies indicate that continuity of carer at the primary care level reduces hospital admissions, improves compliance with treatment, increases preventive care and improves relationships between clinician and patient [41,42]. Maintaining skilled and knowledgeable continuity of carer can be challenging in this context given the high staff turnover and difficulties retaining staff in remote communities [43] but should be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Continuity of carer is a critical component of primary health care known to improve the quality of service delivery [40]. Studies indicate that continuity of carer at the primary care level reduces hospital admissions, improves compliance with treatment, increases preventive care and improves relationships between clinician and patient [41,42]. Maintaining skilled and knowledgeable continuity of carer can be challenging in this context given the high staff turnover and difficulties retaining staff in remote communities [43] but should be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…From a state Medicaid database: Clark et al 6 found that continuity of site for mother in the prenatal period and the infant in the postnatal period (approximately one-half of the infants) was associated with additional well-child and emergency department (ED) visits but no reduction in hospitalizations. This study raises more questions that it answers-we usually hope that continuity, even from mother to infant, helps prevent ED visits.…”
Section: Health Services Deliverymentioning
confidence: 99%
“…Here we highlight studies that provide new/ clarifying results, [1][2][3][4][5] mixed results, [6][7][8] and unexpected results. 6,7 Several reports provide information and data on major tenets of family medicine: Clark et al 6 studied continuity between prenatal care and infant care; Mainous et al 5 described the long-term personal history importance to future risk of disease; and Merenstein and Merenstein 9 provide patient feedback on the importance of the doctor-patient relationship.…”
mentioning
confidence: 99%